Silhouettes in a City: Women, Work and Welfare in Dublin, c. 1890- 1930s - Frehill, Olivia Anne (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2024)
This thesis investigates the position of women workers in Dublin in the period c. 1890-1930s. It focuses on women as employees in paid employment, rather than as business owners, self-employed innovators, house workers, workers within family farms, women engaged in voluntary work or the trailblazers in the more learned professions. It examines working-class and lower middle-class forms of employment. This is a faction of the female workforce that has been generally understudied in the historiography for the period and so examining their position offers a novel perspective on women's paid work. The thesis takes a series of occupational case studies: domestic service; laundressing; factory work; clerking; and teaching. Examination of these different kinds of work illuminates the factors that shaped the female experience and the working world they were embedded in. Archival fragments are used to build up a picture of women's experience of work in the different areas, providing insights into the working worlds behind more general statistics and trends. The focus is on the urban context, specifically Dublin. As a result, the city is threaded through this thesis. The developing proto welfare state measures of the period are also recognised and women's relationship with the state is unpicked through an examination of their position under the 1911 National Insurance Act. Key factors shaping female workers' experiences include gender, class, technological change, and legislative development. The importance of the family in shaping expectations and opportunities is also addressed. The thesis identifies the factors that underlay the decline in some forms of work and the rise in others. Flashes of worker agency punctuate the chapters, but female workers were also clearly constrained by the wider structures of business, society, and state. Trade unionists, religious figures, employers, state, and philanthropic individuals all sought to shape their wider position. Gendered attitudes ensured low pay and a temporary status were often central to their experience. Their working world was also fragmented by class with the manual and knowledge work distinction critical. National insurance was underpinned by certain biases and assumptions regarding women's economic role, but at the same time, conceded a limited economic position to them. This thesis demonstrates change and limited advancements, as well as the attitudes and realities that underpinned continuities, in the world of paid employment for this section of the female workforce.
APPROVED
Keywords: Women's Work; Welfare; Irish History; Social Class; Nineteenth Century History; Twentieth Century History; Dublin